Waste water treatment and reuse in the Mediterranean Region - Barcelo, Damia; Petrovic, Mira (The handbook of environmental chemistry, 2011)
Water scarcity and the need for ecological sustainability have led to the introduction of treated waste water as an additional water resource in the national water resource management plans of Mediterranean countries. Summarizing the results generated within the European Union-funded project INNOVA-MED, this volume highlights the following topics: Application of innovative technologies and practices for waste water treatment and reuse adapted to the Mediterranean region; Constraints on the application of advanced treatments and reuse of reclaimed water and sludge; Problems and requirements of sustainable water management in the Mediterranean area. The book includes several examples of Mediterranean countries, such as Tunisia, Morocco, Egypt, Palestine and Spain, and presents their practical experiences in the application of innovative processes and practices for waste water treatment and reuse.